The influence of different levels of physical activity and sports performance on the accuracy of dynamic lower limbs balance assessment among Chinese physical education college students - Huang, Xuejuan; Yan, Zhiyang; Ma, Yong; Liu, Hua (Frontiers in Physiology, 2023)
Background: Balance ability is the basis of human actions. Improving the accuracy of dynamic balance assessment can increase the efficiency of sports injury prediction. Objectives: This study aimed to investigate how physical activity and sports performance affect the dynamic balance ability of lower limbs and validate whether the Lower Quarter Y-Balance Test (YBT-LQ) is a reliable predictor of sports injury risk among Chinese physical education college students. Materials and Methods: In total, 169 voluntary participants completed the YBT-LQ at the beginning of a semester and provided some physiological information and an injury report at the end of the semester. The correlation between YBT-LQ performance and selected factors that can affect the dynamic balance control was analyzed based on data statistics. The receiver operating characteristic (ROC) and the area under curve (AUC) of the composite scores of the YBT-LQ were calculated to explore an optimal cutoff value for predicting sports injury risk. Results: The composite scores of the YBT-LQ exhibited strong correlations with both the sports performance level and sports injury, as well as a moderate correlation with physical activity level, age (negative), and metabolic equivalent (MET). In the entire study population, the area under the receiver operating characteristic (ROC) curves for the binary classification of composite YBT-LQ scores of the left and right legs to predict sports injury risk were 0.78 and 0.74, respectively. Stratifying the study participants based on their levels of physical activity and sports performance had an effect on the AUC values of ROC curves. The optimal cutoff scores of the YBT-LQ for predicting sports injury risk were variable, with values more or less than 95%. Specifically, the cutoff scores for participants with the highest level of sports performance were notably higher, reaching up to 106.5% (left) and 107.2% (right). Conclusion: Physical activity and sports performance can influence human dynamic balance control. Composite scores of the YBT-LQ can be used with acceptable efficiency to predict sports injury. Stratifying participants based on their levels of physical activity and sports performance leads to different optimal cutoff values of the YBT-LQ composite scores in predicting sports injury. This approach is preferable to relying solely on a uniform 95% cutoff. It is recommended to analyze individuals with higher levels of sports performance, such as elite athletes, separately from those with lower levels. This is because the former group has a higher optimal cutoff value compared to the latter.